The Struggle Life Of A Football Player As Seen In Michael Lewis' Blindside: Evolution Of A Game - Andy Amiruddin Andy Amiruddin; Yudha Pratama Yudha Pratama (Jurnal Ilmiah Pendidikan Scholastic, 2026)
This research examines the psychological struggle of Michael Oher, the central figure in The Blind Side: Evolution of a Game by Michael Lewis, through the lens of Sigmund Freud’s psychoanalytic theory published in 1923. The research aims to analyze how Oher’s personality develops in response to both internal desires and external forces, particularly focusing on the conflict between unconscious drives and societal expectations. Freud’s structural theory of the psyche divided into the id, ego, and superego serves as the main theoretical framework for this analysis. The purpose of the research is to understand how Michael Oher’s traumatic past and complex environment shape his identity and behavior. The study also seeks to explore the role of family, education, and social support in transforming Oher from a silent, emotionally distant boy into a successful athlete and functioning adult. To accomplish this, the research applies a qualitative descriptive method, using close reading as the primary technique for data collection. Selected quotations and scenes from the novel are analyzed to identify patterns that reflect Freud’s psychological concepts. The findings indicate that Oher’s life struggle is heavily influenced by unresolved childhood trauma, represented by the dominance of the id in his early life. Over time, with the intervention of the Tuohy family and exposure to structured environments, his ego and superego gradually develop, allowing him to navigate social expectations and personal goals more effectively. This transformation illustrates how external forces can support psychological development and how Freudian theory can deepen our understanding of character growth in literature